Therapeutic and Scientific Evaluation of the Efficacy of Shatkarma in the Management of Modern Lifestyle Disorders - Tripathi, Piyush mani; kushwah, Sheelendra; kushwah, Khagendra; Antiwal, Meera; Narsimha Murthy, Pro.K.HV.S.S; Tiwari, Ramanand (Journal of Neonatal Surgery, 2025)
The escalating prevalence of non-communicable diseases (NCDs)—such as metabolic syndrome, psychosomatic stress, gastrointestinal dysregulation, and pulmonary disorders—can be directly correlated with the sedentary dynamics, circadian disruption, and heightened psycho-emotional burden of contemporary urban life. Rooted in classical Hatha Yoga treatises, Shatkarma encompasses six foundational purification methodologies: Dhauti, Basti, Neti, Trataka, Nauli, and Kapalabhati. These techniques are traditionally ascribed with systemic detoxificatory potency, promoting somatic homeostasis, neurophysiological optimization, and cognitive-emotional equilibrium. The present inquiry provides a multidisciplinary and evidence-informed exploration into the prophylactic and therapeutic efficacy of Shatkarma in addressing modern lifestyle-induced pathophysiological syndromes. Through critical evaluation of classical yogic doctrine integrated with contemporary clinical insights, this study positions Shatkarma as a potential adjunctive intervention within the framework of integrative and preventive medicine. It underscores the relevance of ancient embodied practices in modulating psychoneuroimmunological functions, enhancing systemic resilience, and advancing holistic health outcomes in the 21st century